Mild expression differences of MECP2 influencing aggressive social behavior. Issue 5 (20th March 2014) - Tantra, Martesa; Hammer, Christian; Kästner, Anne; Dahm, Liane; Begemann, Martin; Bodda, Chiranjeevi; Hammerschmidt, Kurt; Giegling, Ina; Stepniak, Beata; Castillo Venzor, Aracely; Konte, Bettina; Erbaba, Begun; et al.
Abstract The X‐chromosomal MECP2/Mecp2 gene encodes methyl‐CpG‐binding protein 2, a transcriptional activator and repressor regulating many other genes. We discovered in male FVB/N mice that mild ( 50%) transgenic overexpression of Mecp2 enhances aggression. Surprisingly, when the same transgene was expressed in C57BL/6N mice, transgenics showed reduced aggression and social interaction. This suggests that Mecp2 modulates aggressive social behavior. To test this hypothesis in humans, we performed a phenotype‐based genetic association study (PGAS) in >1000 schizophrenic individuals. We found MECP2 SNPs rs2239464 (G/A) and rs2734647 (C/T; 3′UTR) associated with aggression, with the G and C carriers, respectively, being more aggressive. This finding was replicated in an independent schizophrenia cohort. Allele‐specific MECP2 mRNA expression differs in peripheral blood mononuclear cells by 50% (rs2734647: C > T). Notably, the brain‐expressed, species‐conserved miR‐511 binds to MECP2 3′UTR only in T carriers, thereby suppressing gene expression. To conclude, subtle MECP2/Mecp2 expression alterations impact aggression. While the mouse data provides evidence of an interaction between genetic background and mild Mecp2 overexpression, the human data convey means by which genetic variation affects MECP2 expression and behavior.